2016
DOI: 10.1016/j.ebiom.2016.07.030
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Enteropathy: Elusive but Significant Subclinical Abnormalities in Developing Countries

Abstract: Environmental enteropathy/Environmental enteric dysfunction (EE/EED) is a chronic disease of small intestine characterized by gut inflammation and barrier disruption, malabsorption and systemic inflammation in the absence of diarrhea. It is predominantly diseases of children in low income countries and is hypothesized to be caused by continuous exposure to fecally contaminated food, water and fomites. It had not been recognized as a priority health issue because it does not cause overt symptoms and was seen in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(103 citation statements)
references
References 87 publications
2
99
0
2
Order By: Relevance
“…EED typically is clinically silent, that is not manifesting as overt diarrhea [36■,37]. As a clinically asymptomatic disease, intervention to prevent or treat the consequences of EED is problematic.…”
Section: Introductionmentioning
confidence: 99%
“…EED typically is clinically silent, that is not manifesting as overt diarrhea [36■,37]. As a clinically asymptomatic disease, intervention to prevent or treat the consequences of EED is problematic.…”
Section: Introductionmentioning
confidence: 99%
“…Definitive diagnosis of EED is currently by endoscopic biopsy and histology, and the histopathological features indicative of EED include: blunting of villi; increased crypt depth (although some cases show a decrease); reduced villus compartment surface area; increased cellular infiltrate, predominantly lymphocytes and plasma cells; epithelial monolayer fragil ity and breaks; tight junction and cell adhesion abnormalities; and increased epithelial cell shedding 14 . These features are shown in FIG.…”
Section: Diagnosis Of Eedmentioning
confidence: 99%
“…Many other biomarkers have been proposed as candi dates to monitor or diagnose EED (comprehensive reviews are available elsewhere 14,18 ) and new bio markers are constantly being sought, but there is difficulty in obtaining a 'gold standard' measurement for comparison. Two large-scale trials are also currently investigating the effect of community-level water and sanitary health (WASH) 19 improvements on factors including child-length for age, child development scores and stunting prevalence (the SHINE trial in Zimbabwe 20 and the WASH Benefits Trial in Kenya and Bangladesh 21 ).…”
Section: Biomarkers For Eedmentioning
confidence: 99%
“…Emerging evidence has shown that the periphery immune system is Oral, nasal, and skin-patch vaccines have been developed to elicit protective immunity by noninvasive delivery of vaccines to the mucocutaneous interface. Although oral vaccines against polio and cholera have been deployed with varying degrees of success [18], progress to develop oral vaccines is limited owing to multiple obstacles including interference from food particles and gut microbiome, enzymatic digestion of antigens, inefficient antigen delivery across epithelial cells into mucosa-associated lymphoid tissue (MALT) in the gastrointestinal (GI) tract, enteropathy found in developing countries [36,37], as well as the oral mucosal immune system which tends to induce tolerance upon exposure to dietary antigens that trigger the generation of retinoid-related orphan receptor gamma t (RORγt)-deficient regulatory T cells in the GI tract [38]. The demonstration that oral vaccines' efficacy could be improved by targeting intestinal microfold (M) cells with biodegradable microparticles [39] or feeding vaccinees with a buffer solution in advance [40] offers hope for enhancing the potency of oral vaccines.…”
Section: Noninvasive Vaccination As a Juggernaut To Minimize Vaccinatmentioning
confidence: 99%